2018
DOI: 10.1038/s41419-018-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-338-3p functions as a tumor suppressor in gastric cancer by targeting PTP1B

Abstract: Gastric cancer (GC) is one of the most common malignant tumors and peritoneal metastasis is the primary cause for advanced GC’s mortality. Protein-tyrosine phosphatase 1B (PTP1B) functions as an oncogene and involves in carcinogenesis and cancer dissemination. However, the function and regulation of PTP1B in GC remain poorly understood. In this study, we found that PTP1B was upregulated in GC tissues and overexpression of PTP1B in vitro promoted cell migration and prevented apoptosis. Then, we predicted that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 49 publications
5
45
1
Order By: Relevance
“…Previous studies have demonstrated that miR-338-3p could function as a tumor suppressor in GC, NSCLC and CRC. [31][32][33] We also confirmed the anti-carcinogenic effect of miR-338-3p in CRC in this study, and the function of miR-338-3p is inhibited after sponged by SNHG15.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have demonstrated that miR-338-3p could function as a tumor suppressor in GC, NSCLC and CRC. [31][32][33] We also confirmed the anti-carcinogenic effect of miR-338-3p in CRC in this study, and the function of miR-338-3p is inhibited after sponged by SNHG15.…”
Section: Discussionsupporting
confidence: 78%
“…Then, we predicted the potential miRNAs that bind to circ_0038467 using the online database Circinteractome and validated that circ_0038467 acted as a sponge of miR‐338‐3p in 16HBE cells. MiR‐338‐3p has been reported to repress tumorigenesis and progression of multiple human tumors, such as ovarian cancer, gastric cancer and NSCLC . MiR‐338‐3p was also demonstrated to be downregulated in acute kidney injury .…”
Section: Discussionmentioning
confidence: 99%
“…Former works have indicated multiple targets of miR-338-3p, such as protein-tyrosine phosphatase 1B (PTP1B), runt-related transcription factor 2 (RUNX2), cyclin-dependent kinase 4 (CDK4) and Ras-Related Protein 23 (RAB23). [17][18][19] To further elucidate the mechanism of baicalin, this research validated that MORC4 could act as a target of miR-338-3p, revealed by luciferase reporter and RIP assays. The emerging evidence indicated MORC4 as an oncogene in BC, uncovered by which its knockdown suppressed cell growth by promoting apoptosis.…”
Section: Dovepressmentioning
confidence: 96%
“…16 Increasing evidences suggest that miR-338-3p could function as a tumor suppressor by inhibiting proliferation, metastasis and promoting apoptosis in gastric cancer, osteosarcoma and prostate cancer. [17][18][19] In BC, a former work describes that down-regulation of miR-338-3p promotes cell growth, migration and invasion in vitro and contributes to lung metastasis in vivo. 20 Microrchidia family CW-type zinc-finger (MORC) family, including MORC1, MORC2, MORC3 and MORC4, plays pivotal roles in human cancer development.…”
Section: Introductionmentioning
confidence: 99%